A current collector covering nanostructured villous oxygen-deficient NiO fabricated by rapid laser-scan for Li-O2 batteries. (September 2018) - Mu, Xiaowei; Wen, Qiuhao; Ou, Gang; Du, Yuemin; He, Ping; Zhong, Minlin; Zhu, Hong; Wu, Hui; Yang, Sixie; Liu, Yijie; Li, Bojie; Zhang, Xueping; et al.
Abstract: Non-aqueous Li-O2 batteries attract extensive attention because of their ultra-high theoretical specific energy density. However, the high charge potential, which induces severe parasitic reactions such as the corrosion of carbon-based catalysts and metal current collectors, is one of the biggest challenges currently. Herein, a current collector of Ni foam covering nanostructured villous NiO with oxygen vacancies (NiO1-δ ) was fabricated by a fast laser-scan technique. The modified NiO1-δ based current collector presented superior stability and comparable electrocatalytic activity. It delivered a discharge capacity of about 500 mAh g −1 and a low charge potential of 3.84 V in a Li-O2 cell in the absence of catalysts. And this cell could maintain 73.5% of the initial capacity after 100 full discharge-charge cycles. Density functional theory (DFT) calculations verified that the improved electrocatalytic activity mainly derived from the introduction of oxygen vacancies in NiO1-δ . It improved the electronic conductivity for rapid electron transfer as well as served as active sites to bind O2 and oxygen-containing intermediates (eg. LiO2 ) for electrochemistry reactions. This work gives a rapid and easily mass-produced method to fabricate a stable and activated current collector for Li-O2 batteries. Graphical abstract: Nanostructured villous NiO with oxygen vacancies (NiO1-δ ) grown on Ni foam is synthesized as a stable and activated current collector for Li-O2 batteries. Experiments and theoretical calculations demonstrated that the introduction of oxygen vacancies improved the electronic conductivity for rapid charge-transfer and served as active sites to bind reaction species for electrochemistry reactions. fx1 Highlights: The Ni foam covering nano-villous NiO1-δ as a stable and activated current collector for Li-O2 batteries was investigated. The improved activity arriving from oxygen vacancies was demonstrated by experiments and DFT calculations. The existence of oxygen vacancies improved the electronic conductivity and served as active sites. This work gives a rapid and easy method to fabricate a stable and activated current collector for Li-O2 batteries.